Digitalisasi dan Konsep Keterbelakangan: Kajian Ekonomi Politik Media dalam Iklan Telkom - Qoriatul Mahfudloh (LP3M IAI Al-Qolam Malang, 2021)
More than a decade since digital civilization been published among Indonesian, and it is now facing a new challenge. Digital civilization which had been presumed to break through the dichotomy of concepts between the development and the retardation as the modernity consequences, is indeed facing the utopia’s results to the humanity. This premise is induced from advertisement’s the critical study of the one of the greatest telecommunication corporate in Indonesia, Telkom. In this ads, digital concept is being opposed to the concept retardation, which is being one-sided to village-discourse and middle classes profession. This research uses Vincent Mosco’s political economic of media theory. Besides that, the researcher uses critical discourse analysis as method to analyze the media visual data. This research also conducts the process of meaning among referees ‘village’ and ‘middle-class profession’, and also the concept of ‘retardation’.